Polarization-dependent strong coupling between silver nanorods and photochromic molecules - Lamri, Gwénaëlle; Veltri, Alessandro; Aubard, Jean; Adam, Pierre-Michel; Felidj, Nordin; Baudrion, Anne-Laure (Beilstein Journal of Nanotechnology, 2018)
Active plasmonics is a key focus for the development of advanced plasmonic applications. By selectively exciting the localized surface plasmon resonance sustained by the short or the long axis of silver nanorods, we demonstrate a polarization-dependent strong coupling between the plasmonic resonance and the excited state of photochromic molecules. By varying the width and the length of the nanorods independently, a clear Rabi splitting appears in the dispersion curves of both resonators.
Keywords: active plasmonics; photochromic molecules; plasmon; Rabi splitting; strong coupling